A multidisciplinary perioperative strategy for attaining "more physiologic" cardiac surgery. (September 2017) - Anastasiadis, Kyriakos; Antonitsis, Polychronis; Deliopoulos, Apostolos; Argiriadou, Helena
Background: Cardiac surgery is, by definition, a "non-physiologic" intervention associated with systemic adverse effects. Despite advances in surgical technique, cardiopulmonary bypass (CPB) technology as well as anaesthesia management and patient care, there is still significant morbidity and subsequent mortality. Aim: We consider that the contemporary demand for further improving patient outcome mandates the upgrade from optimal perfusion during the procedure as the gold standard to the concept of a "more physiologic" cardiac surgery. Our policy is a multidisciplinary perioperative strategy based on goal-directed perfusion throughout surgery incorporating in-line monitoring. This translates to "prevent rather than correct" malperfusion through real-time adjustment rather than correction of derangement detected late by incremental evaluation. Method: The strategy is based on continuous monitoring of cardiac index, SvO2, DO2 i, DO2 i/VCO2 i and rSO2 . Data acquisition is followed by action when needed; this includes stepwise: transfusion, increase of cardiac output and initiation of inotropic/vasoactive support. Moreover, implementation of minimally invasive extracorporeal circulation (MiECC) is considered as a fundamental component of physiologic perfusion when on-CPB, providing improved circulatory support and end-organ protection. Conclusion: We consider that, with this strategy which establishes optimal perfusion perioperatively, we attain the goal of a "more physiologic" cardiac surgery.